Elasto-plastic state of curve beam system subjected to complex loading - Bay, Vu Khac (Vietnam Journal of Mechanics, 1996)
Investigation of the elastic state of curve beam system had been considered in [3]. In this paper the elastic-plastic state of curve beam system in the form of cylindrical shell is analyzed by the elastic solution method. Numerical results of the problem and conclusion are given.